Optimization of Microwave-Assisted Extraction Process of Total Flavonoids from Salicornia bigelovii Torr. and Its Hepatoprotective Effect on Alcoholic Liver Injury Mice - Dujun Wang; Jing Lv; Yan Fu; Yueling Shang; Jinbin Liu; Yongmei Lyu; Ming Wei; Xiaohong Yu (Foods, 2024)
The objective of this study was to determine the optimal extraction conditions for total flavonoids from S. bigelovii using microwave-assisted extraction and to analyze the protective effect of total flavonoids from S. bigelovii on alcoholic liver injury in mice. The optimization of the process conditions for the microwave-assisted extraction of total flavonoids from S. bigelovii was performed using response surface methodology, and an alcohol-induced acute liver injury model in mice was used to investigate the effects of different doses of total flavonoids (100 mg/kg, 200 mg/kg, and 400 mg/kg) on the levels and activities of serum alanine aminotransferase kits (ALT), glutamic oxaloacetic transaminase kits (AST), superoxide dismutase kits (SOD), glutathione peroxidase kits (GSH-Px), and malondialdehyde (MDA). We performed hematoxylin–eosin (H&E) staining analysis on pathological sections of mouse liver tissue, and qRT-PCR technology was used to detect the expression levels of the inflammatory factors IL-1 β, IL-6, and TNF-α. The results revealed that the optimal extraction process conditions for total flavonoids in S. bigelovii were a material-to-liquid ratio of 1:30 (g/mL), an ethanol concentration of 60%, an extraction temperature of 50 °C, an ultrasound power of 250 W, and a yield of 5.71 ± 0.28 mg/g. Previous studies have demonstrated that the flavonoids of S. bigelovii can significantly inhibit the levels of ALT and AST in the serum (p < 0.001), reduce MDA levels (p < 0.001), increase the activity of the antioxidant enzymes SOD and GSH-Px (p < 0.001), and inhibit the IL-1 β, IL-6, and TNF-α gene expression levels (p < 0.001) of inflammatory factors. The total flavonoids of S. bigelovii exert a protective effect against alcoholic liver injury by reducing the levels of inflammation, oxidative stress, and lipid peroxidation caused by alcohol. The results of this study lay the foundation for the high-value utilization of S. bigelovii and provide new resources for the development of liver-protective drugs.